2006
DOI: 10.1590/s1516-84842006000400007
|View full text |Cite
|
Sign up to set email alerts
|

Deformabilidade eritrocitária na anemia ferropriva

Abstract: A deformabilidade é a característica que permite ao eritrócito normal de 7 a 8 micrômetros (µm) circular por capilares de até 3 µm de diâmetro. Esse fenômeno depende da geometria celular, da viscosidade interna e de propriedades visco-elásticas da membrana eritrocitária. Dentre as técnicas de estudo da deformabilidade eritrocitária (DE), como aspiração por micropipeta, filtração e reoscopia, destaca-se a ectacitometria. Esta técnica utiliza um viscosímetro de fluxo laminar no qual as modificações de forma dos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Some authors suggest that in iron deficiency anemia there is a reduction in the survival of the microcytic and hypochromic RBCs, and that one of the main factors would be their reduced flexibility. This fact would be related to the lower internal hemoglobin content and unfavorable surface/volume ratio of the cell, with consequent early sequestration by the reticuloendothelial system ( Patavino et al , 2006 ). As pequi is rich in iron, this could explain the increase in HGB and HCT and, consequently, the lack of significant differences observed for HGB and HCT in female controls of 11-12 months compared to 6-7 months.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors suggest that in iron deficiency anemia there is a reduction in the survival of the microcytic and hypochromic RBCs, and that one of the main factors would be their reduced flexibility. This fact would be related to the lower internal hemoglobin content and unfavorable surface/volume ratio of the cell, with consequent early sequestration by the reticuloendothelial system ( Patavino et al , 2006 ). As pequi is rich in iron, this could explain the increase in HGB and HCT and, consequently, the lack of significant differences observed for HGB and HCT in female controls of 11-12 months compared to 6-7 months.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier approaches, using rat RBC as a model, demonstrated that this less deformable cell could be a consequence of peroxidation damage to membrane cell lipids or the crosslinking of the membrane proteins [3]. Other authors, using ectacytometry approach, demonstrated a diminished erythrocyte deformability in individuals with iron deficiency anemia [5]. On the other hand, Reinhart [4] using the filter aspiration technique, erythrocyte elongation and membrane elasticity measurement showed that, iron deficient RBCs had a similar deformability to control RBCs.…”
Section: Discussionmentioning
confidence: 99%
“…The iron deficient Red Blood Cell (idRBC) elasticity status is controversial, as, although many rheological studies suggest that RBC deformability is impaired [2][3][4][5], others, however do not confirm these observations [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The need to develop low-cost techniques to evaluate red cell rigidity is a present issue for Hematology because the techniques used are restricted to the countries or regions of the world where they appeared. Throughout Brazil, with the sixth world population, we have news of one single piece of equipment [101]. Moreover, new experimental techniques to measure red cell deformability continuously appear, indicating the inexistence of a universalized method.…”
Section: Discussionmentioning
confidence: 99%